Transparent metamaterial absorber with broadband radar cross‐section (RCS) reduction for solar arrays. Issue 13 (7th September 2020) - Kong, Xiangkun; Jiang, Shunliu; Kong, Lingqi; Wang, Qi; Hu, Haobin; Zhang, Xiang; Zhao, Xing
Abstract : Solar arrays are the primary energy source of the satellite. In this study, a metamaterial absorber for solar arrays with simultaneous high optical transparency and broadband microwave absorption is presented. By tailoring the reflection response of meta‐atoms, 87% absorption performance from 6.8 to 18 GHz is obtained. In the meantime, by employing transparent substrates, including indium tin oxide film and anti‐reflection glass, a maximum of 87% light transmittance is achieved. The absorptivity of the proposed metamaterial absorber is simulated and measured experimentally. Optical transmittance and the effect of transparent metamaterial absorber on the conversion efficiency of the solar array have also been measured. These results fully demonstrate the reliability of the authors' design for solar arrays, which also meet the actual requirements of structural strength, atomic oxygen erosion resistance, weight limitation etc.